Number 4 (June 1977) - R. D. Suttkus; G. Clemmer (Southeastern Fishes Council Proceedings, 1977)
A Status Report on the Bayou Darter, Etheostoma rubrum, and the Bayou Pierre System. By R.D. Suttkus and G. Clemmer, plus News Notes, 4 pp.
Keywords: fishes; Bayou Darter; Etheostoma rubrum; Bayou Pierre System